Proposed conceptual model of mobile numerical application for children with autism - Aziz, N.S.A. (Institute of Electrical and Electronics Engineers Inc., 2016)
Basic literacy and numeracy proficiency are two important skills which prepare and shape students for lifelong learning. This study focuses on numeracy skills for children with autism. It is crucial to conduct this study due to the increasing number of children with autism based on statistics data from the Malaysia Social Welfare Department. Children with autism have a neurological disorder that affects the functioning of the brain and causes problems with thinking, feeling, and language. Thus, a lot of studies have been conducted related to the social and literacy skills of the children with autism. However, numeracy skills are also important to the children and the advancement in mobile technology creates new methods to equip the children with numeracy skills. In order to develop a mobile numerical application that is able to fulfil the needs of these children, a proposed conceptual model will be constructed. The proposed conceptual model consists of learning theories, learning principles, multimedia elements together with colour psychology, number skills, language, gestures and contents. Â© 2015 IEEE.